The relative importance of human resource management practices for a firm's innovation performance - Spyridon Arvanitis; Florian Seliger; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2013)
Human resource management (HRM) practices are generally expected to stimulate a firm's innovation performance. However, which of these practices do really pay off? Based on a unique dataset that includes detailed information for both a firm's innovation activities and different types of HRM practices we find that primarily new workplace organization practices seem to enhance a firm's innovation activities. Flexible practices of working time management and incentive payment schemes show only small effects on both innovation propensity and innovation success. Further training does only affect innovation success, but not innovation propensity. Overall, we find a stronger linkage between innovative HRM practices and innovation propensity than with innovation success.
Keywords: O31; 330; human resource management; workplace organization; innovation performance